Cultural Jamming on Satire Websites as a Form of Digital Democracy - Zaenab Zaenab (2022)
New media or internet-based media has become a platform that contributes to changes in the way and style of modern society accessing and interpreting information. The characteristics of new media which are fast, easy, inexpensive, and have the widespread ability are in fact able to become a forum for its users to expand the spectrum of democracy, especially in the digital era. In this study, researchers focused on satirical website content that included forms of political jamming. Through the method of content analysis, the researcher wants to get a deep understanding of a social phenomenon that has recently developed in the form of satirical websites. Anthony Giddens' structuration approach is used as a basis for analyzing satirical website content as a phenomenon for the realization of digital democracy.